2015
DOI: 10.1038/srep14405
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of gut microbiota by berberine and metformin during the treatment of high-fat diet-induced obesity in rats

Abstract: Accumulating evidence suggests that the gut microbiota is an important factor in mediating the development of obesity-related metabolic disorders, including type 2 diabetes. Metformin and berberine, two clinically effective drugs for treating diabetes, have recently been shown to exert their actions through modulating the gut microbiota. In this study, we demonstrated that metformin and berberine similarly shifted the overall structure of the gut microbiota in rats. Both drugs showed reverting effects on the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

48
394
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 517 publications
(458 citation statements)
references
References 56 publications
48
394
2
4
Order By: Relevance
“…The total excretion was the sum of percentages of 64 Cu in all the waste (∑ 0-t urine + ∑ 0-t feces) during 0-t not at the time point on microbe growth was markedly enhanced with additional surface hydroxyl groups [24,31,38]. The Fol1 NPs in the present paper (C 60 (OH) 7 (O) 8 ) had more peroxo or epoxy groups, while Fol113 NPs (C 60 (OH) 11 (O) 6 ) had more hydroxy groups. Physiochemical characterization showed that Fol113 NPs were more soluble, more hydrophilic, and formed smaller aggregates in water than Fol1.…”
Section: Physicochemical Characterization Of Fullerenol Npsmentioning
confidence: 92%
See 4 more Smart Citations
“…The total excretion was the sum of percentages of 64 Cu in all the waste (∑ 0-t urine + ∑ 0-t feces) during 0-t not at the time point on microbe growth was markedly enhanced with additional surface hydroxyl groups [24,31,38]. The Fol1 NPs in the present paper (C 60 (OH) 7 (O) 8 ) had more peroxo or epoxy groups, while Fol113 NPs (C 60 (OH) 11 (O) 6 ) had more hydroxy groups. Physiochemical characterization showed that Fol113 NPs were more soluble, more hydrophilic, and formed smaller aggregates in water than Fol1.…”
Section: Physicochemical Characterization Of Fullerenol Npsmentioning
confidence: 92%
“…1 and Additional file 1: Figure S1), fullerenol NPs were rich in complex -OH groups including peroxo groups to hydroxy groups and peroxo groups to epoxy groups [31,32]. Fol1 and Fol113 can be expressed by the general formulae C 60 (OH) 7 (O )8 and C 60 (OH) 11 (O) 6 , respectively. There may be furan-and pyran-like structures on fullerenol stereostructures (see Fig.…”
Section: Physicochemical Characterization Of Fullerenol Npsmentioning
confidence: 99%
See 3 more Smart Citations